The Effect of Using STEM Learning Models for Students to Improve Digital Literacy Skills in Elementary Schools - Anisa Fauziyah Suswandari (Research and Innovation in Social Science Education Journal (RISSEJ), 2023)
This study aims to analyze the influence of the use of STEM learning models for students to improve digital literacy skills in elementary schools. The method used in this study is quantitative research with a correlational design. The subject of the study was one hundred and ten respondents consisting of two schools, namely public elementary school (SD Negeri 2 Grenggeng and SD Negeri 1 Tanggeran). The research instrument uses questionnaires and the data are tested using validity tests and reliability tests. With the use of STEM learning models in the application of digital literacy, the results are homogeneous and correlated. The results showed that the use of STEM learning models can improve students' digital literacy skills. The use of STEM learning models can be implemented in science, mathematics, and language subjects.